Systematic review of variables that moderate and/or mediate the relationship between child maltreatment and adverse outcomes: a study protocol - Denise Colley; Ertan Mayatepek; Freia De Bock; Lena Rasch; Jenny Seidler; Britta Gahr; Lisa Küppers (BMJ Open, 2024)
Introduction Child maltreatment (CM) is associated with adverse cognitive, behavioural, physical and social outcomes that often continue until adulthood. Systematic reviews on mediators and moderators of this relationship mostly investigate childhood adversities in general or only with regard to an adult population, single outcomes or single forms of maltreatment. The purpose of this review is to synthesise the evidence of variables that mediate and/or moderate the relationship between CM and diverse outcomes.Method A systematic search will be performed in Scopus, PsychInfo, Medline and Web of Science until January 2022. Eligibility criteria include children under 18 years who have been maltreated and experienced adverse outcomes until the age of 21, moderators and/or mediators that influence the relationship between maltreatment and adverse outcomes must belong to the individual level and be amenable to change. After independent screening of studies by two reviewers, data extraction and study quality of included studies will be done using adapted checklists of similar reviews, the Strengthening the Reporting of Observational Studies in Epidemiology report, the COnsensus‐based Standards for the selection of health Measurement INstruments checklist and Downs and Black Checklist. The results will be presented in narrative form and, if adequate, meta-analysis.Ethics and dissemination Ethics approval will not be required. The results of this systematic review will be submitted for publication in a peer-reviewed journal.PROSPERO registration number CRD42022297982.